Structural, magnetic and magnetoelectric properties of Co2Fe2Ta2O9, a TN=53 K honeycomb antiferromagnet. Issue 13 (6th April 2022) - Maignan, Antoine; Martin, Christine
Abstract: The bimetallic oxides of general M4 M'2 O9 formula, where M=Fe, Co, Mn and M'=Nb or Ta, form a family of linear magnetoelectric materials, for which properties depend on the nature of the M, M' pair. In the present study, the structural, magnetic and magnetoelectric properties of a new member, Co2 Fe2 Ta2 O9, synthesized in polycrystalline form, are reported. This compound crystallizing in the P ‐3 c 1 trigonal '429' structure ( a =5.2009 (1) Å, c =14.1986(1) Å and V =332.613(2) Å 3 ) is found to be antiferromagnetic below TN =53 K. Although the structural features are intermediate between the Co4 Ta2 O9 and Fe4 Ta2 O9 limit members, a very different magnetoelectric behaviour is observed. In order to reveal the differences between M4 M'2 O9 with M=Fe or Co or mixed and M'=Ta or Nb, a comparison between these six compounds is proposed. Abstract : Evolution of the Néel temperature TN as a function of the unit cell volume V for the Fe4‐x Cox Ta2 O9 and Fe4‐x Cox Nb2 O9 samples.